Palliative Care Based-on Family-Centered Nursing Affects the Level of Dependency of The Patients Undergoing Hemodialysis - Virgianti Nur Faridah; Isni Lailatul maghfiroh; Aprelia Afidatul Hanafi; Rizky Asta Pramestirini; Trijati Puspita Lestari (The Indonesian Journal of Health Science, 2021)
Background: Hemodialysis is a burdensome and complex therapy, which can cause physical and psychological stress and has an impact on the patient's level of dependence in the patient's daily activities. The purpose of this study was to determine the relationship between palliative care based on family-centered nursing and the level of dependence of patients with chronic kidney disease on hemodialysis at Ibnu Sina Gresik General Hospital.Method: This research design uses a correlational analytic method with a cross-sectional approach. The population is patients and their families with chronic kidney disease on hemodialysis. The samples were taken using a consecutive sampling technique of 120 patients and their families. Data were taken using a questionnaire. Data analysis using Spearman rank correlation test.Result: The results showed that 43 (35.8%) families had adequate family-centered nursing-based palliative care skills and 107 patients (89.1%) had mild dependence. The results of the analysis using the Spearman test showed a correlation coefficient of -0,348 with a significant value of 0.007 with = 0.05 then H1 was accepted, which means that there is a relationship between family-centered nursing-based palliative care on the level of dependence of chronic kidney disease patients with hemodialysis in Ibnu Sina Gresik General Hospital.Conclusion and Recommendation: Patients with Chronic Kidney Disease who begin to experience dependence in fulfilling their daily activities need family-centered nursing-based palliative care skills by the family.